Communication, Social Media and Adolescence: The Use of Social Media in Adolescent Communication in the Basque Country and Navarre - Peña Sarrionandia, Mikel; Narbaiza Amillategi, Bea; Arana Arrieta, Edorta; Zorita Aguirre, Itziar (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
This article examines how adolescents in the Basque Country and Navarre use social media in their daily communication. The findings highlight the integration of these tools into the social lives of youth and a general preference for face-to-face interactions for more personal topics. However, the study also reveals how digital platforms influence in-person dynamics, emphasizing the importance of balancing both communication modes and fostering a critical and responsible approach to social media.